Beginner gardening step by step : a visual guide to yard and garden basics (DK Publishing, 2019)
"Is your lawn full of weeds? Are your fruits and vegetables diseased? Is your flower bed forlorn? Do you long to create an outdoor space you can enjoy with friends--or even a garden you can show off with pride? Provides the basics you need to get your green space under control and keep it that way. Plus lots of simple garden ideas you can do yourself. With step-by-step photographs. From planting decorative climbers to growing your own tomatoes, these easy steps will make a big difference in how your garden and landscape look and feel. Take the anxiety out of planting, potting, and pruning and enjoy your lush lawn, beautiful landscape, and bountiful garden."--Back cover.